Genome-wide Phenotypic Profiling Identifies and Categorizes Genes Required for Mycobacterial Low Iron Fitness - Dragset, Marte S. (Sci Rep, 2019)
Iron is vital for nearly all living organisms, but during infection, not readily available to pathogens. Infectious bacteria therefore depend on specialized mechanisms to survive when iron is limited. These mechanisms make attractive targets for new drugs. Here, by genome-wide phenotypic profiling, we identify and categorize mycobacterial genes required for low iron fitness. Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis (TB), can scavenge host-sequestered iron by high-affinity iron chelators called siderophores. We take advantage of siderophore redundancy within the non-pathogenic mycobacterial model organism M. smegmatis (Msmeg), to identify genes required for siderophore dependent and independent fitness when iron is low. In addition to genes with a potential function in recognition, transport or utilization of mycobacterial siderophores, we identify novel putative low iron survival strategies that are separate from siderophore systems. We also identify the Msmeg in vitro essential gene set, and find that 96% of all growth-required Msmeg genes have a mutual ortholog in Mtb. Of these again, nearly 90% are defined as required for growth in Mtb as well. Finally, we show that a novel, putative ferric iron ABC transporter contributes to low iron fitness in Msmeg, in a siderophore independent manner.